2009
DOI: 10.7249/op256
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Threats and Security Planning: How Should We Decide What Hypothetical Threats to Worry About?

Abstract: This document and trademark(s) contained herein are protected by law as indicated in a notice appearing later in this work. This electronic representation of RAND intellectual property is provided for non-commercial use only. Unauthorized posting of RAND PDFs to a non-RAND Web site is prohibited. RAND PDFs are protected under copyright law. Permission is required from RAND to reproduce, or reuse in another form, any of our research documents for commercial use. For information on reprint and linking permission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…As Garthoff notes in an article on intelligence estimates, "it would be foolish to base our judgements only on what they say, and not also on what they do" [Garthoff, (1978), p.26]. It is here where the balance between capability and intentions comes into play as intentions themselves may in fact be limited by an opponent's resources, perception of risk, experience, and so on (Jackson and Frelinger, 2009;Schneier, 2006;Stech and Hoffman, 1982). The importance of focusing on intentions and capability is borne out by a study on success and failure in terrorist operations which found, not entirely surprisingly, that when there is a mismatch between intention and capability there is a higher likelihood of failure (Jackson and Frelinger, 2009).…”
Section: Intentionsmentioning
confidence: 99%
See 4 more Smart Citations
“…As Garthoff notes in an article on intelligence estimates, "it would be foolish to base our judgements only on what they say, and not also on what they do" [Garthoff, (1978), p.26]. It is here where the balance between capability and intentions comes into play as intentions themselves may in fact be limited by an opponent's resources, perception of risk, experience, and so on (Jackson and Frelinger, 2009;Schneier, 2006;Stech and Hoffman, 1982). The importance of focusing on intentions and capability is borne out by a study on success and failure in terrorist operations which found, not entirely surprisingly, that when there is a mismatch between intention and capability there is a higher likelihood of failure (Jackson and Frelinger, 2009).…”
Section: Intentionsmentioning
confidence: 99%
“…This type of thinking may be a common element after cases of strategic surprise (Betts, 2007). As such, perceived 'failures of imagination' seen as a causal factor in the failure to stop the 9/11 attacks from occurring meant that food defence and other 'exotic' terrorist threats became far more salient (Jackson and Frelinger, 2009).…”
Section: The Perception Of Threatmentioning
confidence: 99%
See 3 more Smart Citations